DRY COTTON IN COTTON CLEANING ENTERPRISES, FIBER WETTING TECHNIQUE AND TECHNOLOGY (Web of Technology: Multidimensional Research Journal, 2024)
This article presents modern methods and devices for wetting dry cotton, fiber in cotton refineries. It is known to us that in the process of processing cotton, the dryness rate of cotton is 8%, while the dryness rate is normal. In the process of processing cotton, the quality of the produced product will be at a high level if the degree of dryness of the cotton is in moderation.